Left Main Disease and Bifurcation Percutaneous Coronary Intervention: Focus on Antithrombotic Therapy - Charalampos Varlamos; Ioannis Lianos; Despoina-Rafailia Benetou; Dimitrios Alexopoulos (US Cardiology Review)
Revascularization of both left main and bifurcation lesions is currently considered an important feature of complex percutaneous coronary intervention (PCI), whereas stenting distal left main bifurcation is fairly challenging. Recent evidence shows that such lesions are associated with an increased risk of ischemic events. There is no universal consensus on the optimal PCI strategy or the appropriate type and duration of antithrombotic therapy to mitigate the thrombotic risk. Prolonged dual antiplatelet therapy or use of more potent P2Y12 inhibitors have been investigated in the context of this high-risk subset of the population undergoing PCI. Thus, while complex PCI is a growing field in interventional cardiology, left main and bifurcation PCI constitutes a fair amount of the total complex procedures performed recently, and there is cumulative interest regarding antithrombotic therapy type and duration in this subset of patients, with decision-making mostly based on clinical presentation, baseline bleeding, and ischemic risk, as well as the performed stenting strategy.